Violet Balestreri Archer: Milestones of a Career (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
Un article de la revue Canadian University Music Review / Revue de musique des universités canadiennes, diffusée par la plateforme Érudit.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes

Musica E Poesia Nell’ Opera di Violet Archer [Musique et poésie dans l'œuvre de Violet Archer] - Calo, Francesca (Université de Rome « La Sapienza », 1995)
Keywords: Pas de lien web

The Composer's Voice: "What women can do" - Dalen, Brenda (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
In this interview, conducted on 18 August 1994, Violet Balestreri Archer revisits her past, recreating the experiences of her youth from the earliest days of her childhood in Como and Montreal to her graduation from Yale University in 1949 and sharing highly personal memories of her family, teachers, and friends. She recalls her first visit to Italy, her school years, her piano lessons, her early attempts at composition, her participation in the Montreal Women's Symphony, and her compositional studies with Douglas Clarke at McGill University, Béla Bartók in New York, and Paul Hindemith at Yale University. In listening to her story, we discover "who" she is and "how" she succeeded in establishing her compositional voice and in creating a space or "room" for herself in a profession traditionally dominated by men.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes

The emergence of a new reality for Quebec Women Composers - Lefebvre, Marie-Thérèse (With a Song in Her Heart: A Celebration of Canadian Women Composers, 1995)

Creating Worlds For Music To Exist: How Women Composers of Electroacoustic Music Make Place For Their Voices - McCartney, Andra (Université York, 1995)

Whose Playground, Which Games and What Rules?: Women Composers in the Digital Playground - McCartney, Andra (International Composer Music Association, 1995)
Keywords: Pas de lien web